Developments In the distinction between principal and accessorial liability In light of the first case law of the international criminal court (2009)
The distinction between perpetration of a crime, which gives rise to principal liability, and participation in a crime committed by a third person, which gives rise to accessorial liability, responds to the distinction between those who are directly liable for the violation of a penal norm (perpetrators or principals to the crime) and those others who are derivatively liable (accessories to the crime or secondary parties).Although this distinction is embraced by most national criminal law systems there are a few national systems (in particular Denmark and Italy) usually referred